Synthesis and characterization of ultralong SiC nanowires with unique optical properties, excellent thermal stability and flexible nanomechanical properties - Ping Hu (Nature Portfolio, 2017)
Abstract Several-millimeter long SiC nanowires (NWs) with unique optical properties, excellent thermal stability and flexible nanomechanical properties were synthesized using a simple method with silicon and phenolic resin as the raw materials. The SiC NWs displayed special optical properties that were attributed to their large size and Al-doping. They displayed broad green emission at 527.8 nm (2.35 eV) and purple emission concentrated at 438.9 nm (2.83 eV), in contrast to the other results, and the synthesized SiC NWs could also remain relatively stable in air up to 1000 °C indicating excellent thermal stability. The Young’s moduli of the SiC NWs with a wide range of NW diameters (215–400 nm) were measured using an in situ nanoindentation method with a hybrid scanning electron microscopy/scanning probe microscopy (SEM/SPM) system for the first time. The results suggested that the values of the Young’s modulus of the SiC NWs showed no clear size dependence, and the corresponding Young’s moduli of the SiC NWs with diameters of 215 nm, 320 nm, and 400 nm were approximately 559.1 GPa, 540.0 GPa and 576.5 GPa, respectively. These findings provide value and guidance for studying and understanding the properties of SiC nanomaterials and for expanding their possible applications.